Supramolecular organization and materials design (Cambridge University Press, 2002)
This reference demonstrates the seminal importance of supramolecular chemistry and self-organization in the design and synthesis of novel organic materials, inorganic materials, and biomaterials. It shows how the bottom-up approach of supramolecular chemistry can be used not only to synthesize new materials, but to operate specific molecular devices. It highlights some current aspects of materials synthesis where Supramolecular organization plays a significant role